Pollination of Cretaceous flowers - Bao, Tong (Proc Natl Acad Sci U S A, 2019)
Insect pollination of flowering plants (angiosperms) is responsible for the majority of the world’s flowering plant diversity and is key to the Cretaceous radiation of angiosperms. Although both insects and angiosperms were common by the mid-Cretaceous, direct fossil evidence of insect pollination is lacking. Direct evidence of Cretaceous insect pollination is associated with insect-gymnosperm pollination. Here, we report a specialized beetle-angiosperm pollination mode from mid-Cretaceous Burmese amber (99 mega-annum [Ma]) in which a tumbling flower beetle (Mordellidae), Angimordella burmitina gen. et sp. nov., has many tricolpate pollen grains attached. A. burmitina exhibits several specialized body structures for flower-visiting behavior including its body shape and pollen-feeding mouthparts revealed by X-ray microcomputed tomography (micro-CT). The tricolpate pollen in the amber belongs to the eudicots that comprise the majority of extant angiosperm species. These pollen grains exhibit zoophilous pollination attributes including their ornamentation, size, and clumping characteristics. Tricolpate pollen grains attached to the beetle’s hairs are revealed by confocal laser scanning microscopy, which is a powerful tool for investigating pollen in amber. Our findings provide direct evidence of insect pollination of Cretaceous angiosperms, extending the range insect-angiosperm pollination association by at least 50 million years. Our results support the hypothesis that specialized insect pollination modes were present in eudicots 99 million years ago.